Determination of trigonometric Fourier’s series by the method of four-dimensional mathematics - A. T., Rakhymova; Ahmedov, Anvarjon A.; K. M., Shapen (IOP Publishing Ltd, 2021)
This paper is devoted to the determination of the trigonometric Fourier series by the method of four-dimensional mathematics. In this paper, a new four-dimensional method for evaluation of the sums containing trigonometric function is proposed. Current work provides a first study and finding towards Fourier's series in four-dimensional space.